2003
DOI: 10.1021/jf0205817
|View full text |Cite
|
Sign up to set email alerts
|

Drying Temperature and Relative Humidity Effects on Wheat Gluten Film Properties

Abstract: The mechanical and physical properties of glycerol-plasticized wheat gluten films dried at different temperatures (20, 50, and 80 degrees C) and relative humidities (35 and 70% RH) were investigated. Dispersion of wheat gluten was prepared at pH 11 in aqueous solution. Films were obtained by casting the wheat gluten suspension, followed by solvent evaporation in a temperature and relative humidity controlled chamber. Decreasing relative humidity altered most of the mechanical properties. At 35% RH, tensile str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 34 publications
3
34
0
1
Order By: Relevance
“…For gluten films, Kayserilioğlu et al (2003) found changes in tensile strength and elongation as a function of temperature and RH.…”
Section: Effect Of Glycerol Content and Drying Conditions On Mechanicmentioning
confidence: 99%
“…For gluten films, Kayserilioğlu et al (2003) found changes in tensile strength and elongation as a function of temperature and RH.…”
Section: Effect Of Glycerol Content and Drying Conditions On Mechanicmentioning
confidence: 99%
“…The method described by Kayserilioglu et al, (2003) was used, with minor modification, for the preparation of the wheat gluten films. Deionized water was mixed with 2% wt.…”
Section: Wheat Gluten Bionanocomposites Preparationmentioning
confidence: 99%
“…It is composed of beta-1, 4-linked d-xylose backbone substituted with l-arabinose, d-galactose, acetyl, feruloyl and glucuronic acid residues. Because of its heteropolysaccharidic nature, xylan can be used as a substrate for the production of many important products like xylose [3][4][5], xylitol [6][7][8], biodegradable films [9][10][11], antioxidants [12,13] and xylooligosaccharides [14][15][16][17][18]. Chemical hydrolysis of xylan may lead to the production of hazardous byproducts.…”
Section: Introductionmentioning
confidence: 99%